Implementation of Character Education in the Mathematics Learning Process - Almira Amir (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2022)
The decline in the character of students today is due to the impact of the flow of globalization of information and technology such as no passion in learning, noisy when the teacher explains, low self-confidence, lack of sense of responsibility for the tasks given by the teacher, and tends to be passive so we need a new changes to implement character education in the mathematics learning process.This study aims to determine the implementation of character education in the mathematics learning process, to find out the obstacles to implementing character education in the mathematics learning process, and to find out strategies to overcome obstacles in implementing character education in the mathematics learning process in class X MAS Hajijah Amalia Sari Padangsidimpuan.This research is a qualitative research with the approach used is descriptive ethnography. The primary data sources were the mathematics teacher and class X student of MAS Hajijah Amalia Sari Padangsidimpuan. Data collection techniques are observation, interviews and documentation.The results showed that character education for students in class X MAS Hajijah Amalia Sari Padangsidimpuan had been applied in the mathematics learning process. Specific findings obtained are a lack of student motivation, lack of enthusiasm for learning, lack of infrastructure and lack of time discipline. The strategy in overcoming these obstacles is to familiarize students with applying character values, providing good examples, giving warnings, making conditioning such as posters or slogans that show character values and completing infrastructure facilities that can build character education values in the mathematics learning process.